Analysis of Bearing Contact Characteristics of Face Gear Drives with Coupling Installation Errors - Weng Dengyan; Shen Yunbo; Xu Weijun (Jixie chuandong)
A modeling method of finite element model for precise assembly of face gear transmission with installation error coupling was studied, and the bearing contact characteristics of face gear transmission were analyzed. The discrete points of the tooth surface of the face gear and the cylindrical gear and the assembly angle of the gear pair with installation error were obtained by the numerical calculation method, and the high-precision modeling and assembly of the finite element model of the face gear transmission were realized. Through the secondary development of Abaqus, the finite element bearing contact analysis results and bearing contact characteristic parameters of face gear with installation error coupling were obtained. The results show that when the shaft angle error is too large, the stress concentration will occur, and the contact stress of the tooth surface increases by 41.33％ compared with that without error. When the axial installation error exceeds 0.4 mm, the tooth surface meshing will produce interference. In the case of the coupling of offset and axial installation error, the influence of axial installation error on the bearing contact characteristics is the same as that of the axial installation error when the offset installation error is kept constant.